2014
DOI: 10.1159/000360773
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Severity of Gitelman Syndrome Determined by Serum Magnesium

Abstract: Background/Aims: Normomagnesemia is considered atypical in Gitelman syndrome (GS). Here, we describe clinical, pathological and genetic characteristics in Chinese GS patients with or without hypomagnesemia in order to determine whether serum magnesium concentration indicates the severity of the disease. Methods: 7 normomagnesemic and 25 hypomagnesemic GS patients who were confirmed by direct sequencing of SLC12A3 gene were included. Clinical manifestation and laboratory tests were documented. Supine and uprigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 30 publications
1
36
0
1
Order By: Relevance
“…A blunt reaction to HCT indicated impaired reabsorption function of the DCT. The relationship between the NCC disorder and the clinical manifestations of GS was shown in our previous studies [15, 17, 18]. Because of the limited sample size, we didn’t find significant association between genotype and phenotype, nor the relationship between PGE2 levels and the mutations (including the type of mutations: homozygous, compound heterozygous and heterozygous; locations of NCC protein encoding by different mutations: cytoplasmic sequence, transmembrane regions, intracellular or extracellular).…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…A blunt reaction to HCT indicated impaired reabsorption function of the DCT. The relationship between the NCC disorder and the clinical manifestations of GS was shown in our previous studies [15, 17, 18]. Because of the limited sample size, we didn’t find significant association between genotype and phenotype, nor the relationship between PGE2 levels and the mutations (including the type of mutations: homozygous, compound heterozygous and heterozygous; locations of NCC protein encoding by different mutations: cytoplasmic sequence, transmembrane regions, intracellular or extracellular).…”
Section: Discussionmentioning
confidence: 61%
“…The SLC12A3 gene encoding the NCC was sequenced directly as we previously described [17]. Briefly, genomic DNA was isolated and purified from peripheral blood lymphocyte of the patients and used for polymerase chain reaction amplfication of individual exons of the SLC12A3 gene.…”
Section: Methodsmentioning
confidence: 99%
“…Our analysis based on the previous reports showed that GS patients with lower potassium were more symptomatic, and usually had a younger age at diagnosis and lower serum magnesium level. It has been reported the co‐localization of NCCT and TRPM6 proteins , which might indicate the functional status of NCCT might regulate the Mg 2+ channel TRPM6.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the SLC12A3 mutations scattered through the whole coding sequence of the NCCT protein, but most of the mutations are frequently found in the intracellular domains of the protein [30], and the phenotype of GS is highly heterogeneous [11]. Jiang et al found the percentage of mutated alleles distributed extracellularly was greater in hypo-than normomagnesemic patients [17]. In our review of Chinese GS, most of the SLC12A3 mutation alleles were located on the intracellular domains of NCCT, and we found the average serum potassium and magnesium was significantly lower in subjects with SLC12A3 mutations extracelluarly than those with mutations intracellularly or transmembranally ( Table 2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation